Analisis Penerapan Transparansi Dan Akuntabilitas Dalam Pengelolaan Keuangan Desa Berdasarkan Permendagri No. 20 Tahun 2018 Pada Desa X Kabupaten Bogor - Nurmalasari; Ulupui, I Gusti Ketut Agung; Michael Musyaffi, Ayatulloh (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the implementation of transparency and accountability in village financial management based on the Minister of Home Affairs Regulation No. 20/2018 in Village X, Bogor Regency. This research uses a type of qualitative research with a field case study approach that uses primary data sources obtained from interviews with village officials and villagers, as well as secondary data obtained by collecting documentation and documents in X Village. The results of this study conclude that transparency and accountability in Village X are largely in accordance with the indicators of the Minister of Home Affairs Regulation Number 20 of 2018, but there are still some that are not in accordance with indicators such as accountability indicators in the planning stage and implementation stage. As well as on the transparency indicator, namely Village X does not yet have a website or good information media to convey information disclosure in village financial management